Hydroxychloroquine as Prophylaxis for COVID-19: A Review - Monti, Manuela; Vertogen, Bernadette; Masini, Carla; Donati, Caterina; Lilli, Claudia; Zingaretti, Chiara; Musuraca, Gerardo; De Giorgi, Ugo; Cerchione, Claudio; Farolfi, Alberto; Cortesi, Pietro; Viale, Pierluigi; et al. (Frontiers in Pharmacology, 2020)
In COVID-19 pandemic hera it’s crucial to search for effective drugs and vaccines. Up to now no drugs for disease prophylaxis have been approved yet, despite specific initiatives for acceleration of development support and evaluation procedures for COVID-19 treatments and vaccines. Based on repositioning strategy, we reviewed the state of the art of a promising and controversial drug, Hydroxychloroquine (HCQ), to give a scientific and methodologically correct view of its role, avoiding being influenced by suggestions not evidence based supported. In the present study, we reviewed literature and available data on the prophylactic use of HCQ, one drug of choice for large scale use due to its availability, proven safety and low cost. We therefore make a review of all preclinical and clinical published data, as well as all ongoing Clinical Trials from the bigger clinical trials repositories. From published data, mainly preclinical data are availabe while clinical data are lacking; regarding Clinical Trials search, we found 66 CTs with a multiplicity of schedules indicating how far we are from a standard of care. On 66 CTs, 95% are randomized, 49% are of phase 3 or 2/3; among those randomized, the comparator is represented by placebo or control in 48 clinical trials (76%). Fourty CTs (61%) expect to enroll up to 1000 subjects and 43 CTs (65%) plan to enroll healthcare workers (HCW). Regarding drug schedule, 39 CTs (59.1%) foresee a loading dose while 16 CTs (24.2%) do not expect loading dose; the loading dose is 800 mg in 17 trials (43.6%), 400 mg in 17 (43.6%), 600 mg in 3 (7.7%) and 1200 mg in 1 (2.6%). 35 trials include at least one daily schedule while 17 at least one weekly schedule. 36 trials (54.5%) have a duration of more than 30 days. Awaiting for further developments that could only derive from these prospective randomized clinical trials, the take home message is that a correct methodological approach must always win.